Tourist Perceptions on Brand Equity for Authentic Product: Specific Case of Traditional Culinary in Karawang, West Java - YUSUF, Abdul; MUSLIHAT, Asep; FADILI, Dadan A. (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
The research is aimed to obtain a comprehensive description of brand equity of authentic-culinary product which is (roasted fish wrapped in a banana leaf) that is mostly found in Karawang as the original culinary food. The samples of this research are the visitors of tourism destinations in Karawang who come to traditional restaurants serving the traditional food. Factor analysis is used as data analysis technique to find determinant factors of this research object. In overall, brand equity of traditional culinary food has better level compared to its awareness and loyalty level. As a matter of fact, the customer trust of traditional restaurant is still in unpromising level. In other hands, all of the brand equity dimensions have significant causality level in creating brand equity. Image and trust become strong and significant dimensions in making loyalty.